2022
DOI: 10.1021/acsomega.1c07376
|View full text |Cite
|
Sign up to set email alerts
|

Phase Change Material with Gelation Imparting Shape Stability

Abstract: Blending two gelators with different chemistries (12-hydroxystearic acid and a bis-urea derivative, Millithix MT-800) was used to impart shape stability to CrodaTherm 29, a bio-based phase change material (PCM), melting/crystallizing at near-ambient temperature. The gelators immobilized the PCM by forming an interpenetrating fibrillar network. 15 wt % concentration of the gelators was found to be effective in preventing liquid PCM leakage. In order to improve the mechanical properties and thermal conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Latent Heat Thermal Energy Storage Systems (LHTESS), incorporating phase change material (PCM)-based heat exchangers, offer a promising solution. LHTESS enhances the efficiency and reliability of dry cooling systems, particularly beneficial in arid areas prone to significant temperature swings and power generation challenges [55].…”
Section: Thermoelectric Power Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Latent Heat Thermal Energy Storage Systems (LHTESS), incorporating phase change material (PCM)-based heat exchangers, offer a promising solution. LHTESS enhances the efficiency and reliability of dry cooling systems, particularly beneficial in arid areas prone to significant temperature swings and power generation challenges [55].…”
Section: Thermoelectric Power Generationmentioning
confidence: 99%
“…Hybrid gelling agents combine traditional and nanomaterials for superior thermal properties, while customization for specific PCM materials optimizes phase change temperature and viscosity. Sustainability is emphasized through biomass-derived or waste-material gelling agents, aligning with broader environmental goals [55].…”
Section: Recent Developments In Gelling Agentsmentioning
confidence: 99%
“…In this work, PU was synthesized from poly(caprolactone) (PCL) diol ( M n = 2000 g/mol), castor oil (CO), and tolylene‐2,4‐diisocyanate (TDI) (Scheme 1) in bulk, where PCL 15d and CO 15a,15c will contribute to sustainability due to their degradability and natural resources, respectively. Recently, Zussman et al 16 and Zhai et al 17 pointed out that chemical and physical (hydrogen bonding) crosslinking, respectively, prevented the leakage and influenced the enthalpies (melting and crystalization) of PCMs. SCF is a very suitable material for hydrogen bonding with PU, as reported by Chen et al 5 Earlier, a copolymer of crosslinked poly(glycidyl methacrylate) (PGMA) had been employed in the context of phase change materials by Liu et al 9b Kallitsis et al demonstrated the establishment of a chemical bond between collagen hydrolysate derived from tannery waste and the epoxide ring of GMA, 18 thus validating the feasibility of utilizing leather waste (LW) directly, without requiring purification, as a gelator through hydrogen bonding (Figure 1c) and PGMA as a chemical crosslinker (Figure 1d).…”
Section: Introductionmentioning
confidence: 99%